Application of injectable hydrogels in cancer immunotherapy - Liu, Chutong; Liao, Yingying; Liu, Lei; Xie, Luoyijun; Liu, Junbo; Zhang, Yumao; Li, Yuzhen (Frontiers in Bioengineering and Biotechnology, 2023)
Immunotherapy is a revolutionary and promising approach to cancer treatment. However, traditional cancer immunotherapy often has the disadvantages of limited immune response rate, poor targeting, and low treatment index due to systemic administration. Hydrogels are drug carriers with many advantages. They can be loaded and transported with immunotherapeutic agents, chemical anticancer drugs, radiopharmaceuticals, photothermal agents, photosensitizers, and other therapeutic agents to achieve controlled release of drugs, extend the retention time of drugs, and thus successfully trigger anti-tumor effects and maintain long-term therapeutic effects after administration. This paper reviews recent advances in injectable hydrogel-based cancer immunotherapy, including immunotherapy alone, immunotherapy with combination chemotherapy, radiotherapy, phototherapy, and DNA hydrogel-based immunotherapy. Finally, we review the potential and limitations of injectable hydrogels in cancer immunotherapy.